Biochemical Composition Polymnia sonchifolia Poepp. at the Double Cutting - Andrushchenko, Olena Leonidivna; Vergun, Olena; Fishchenko, Valentyna; Mishchenko, Lidiya (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
Cultivation of Polymnia sonchifolia Poepp. in Ukraine does not guarantee a stable crop of root tubers, therefore, we are studied the possibility of using aboveground biomass of plants. Both tubers and extract of leaves reveal hypoglycemic effect (Kim et al., 2010). Plants of P. sonchifolia cv. Yudinka were used in this study. Leaves mass was cut twice on season to obtain maximal quantitative of plant raw material. The absolutely dry matter was determined by drying of plant raw material to constant mass; total content of sugars – by Bertrand method; concentration of ascorbic acid (AA) – by a 2.6-dichlorophenol-indophenol method; concentration of total carotene – using extraction with rubber solvent (petrol); the total lipid content was extracted with petroleum ether in Soxhlet extractor. The productivity of plant raw material at the double cutting was 22 t/ha, whereas at the cutting once on season was obtained 12 t/ha. Cutting promotes rejuvenation of plants and stimulates synthesis of biologically active compounds. In this case was observed increasing of yield of plants, content of dry matter and basic biochemical compounds of plants. Potential yield of content of dry mass of two cuttings were 3.08 t/ha, while one cutting 2.16 t/ha. Total content of sugars was higher in the young organs of shoot. Content of AA was higher in young leaves in the August than in October – 302.68 and 201.37 mg% respectively. The content of carotene decreased from 4.01 to 0.62 mg% during summer-autumn growing period. Quantity of lipids wasn’t significant (1.25–3.60 %), but the most content was found in the leaves.